Milestone: Ghazi Bisheh (1945–2022) - Hamarneh, Catreena (The Biblical archaeology review, 2022)
On January 24, 2022, the archaeological community in Jordan lost Ghazi Bisheh, an ardent scholar who devoted almost half a century to archaeological research. During his undergraduate studies at the University of Jordan, he became fascinated with archaeology, and in 1970 he left Jordan to earn a master’s degree in Islamic art and architecture […]